2017
DOI: 10.1177/1468087417733865
|View full text |Cite
|
Sign up to set email alerts
|

Development of laser-induced fluorescence to quantify in-cylinder fuel wall films

Abstract: Laser-induced fluorescence of a fuel tracer is a very sensitive technique to image in-cylinder liquid fuel films, but quantification of the measured film thickness has proven difficult so far. This article describes improvements in the quantification procedure and presents an example application in a motored, optically accessible spark-ignition engine with direct injection. We designed a calibration tool that could be pressurized and heated, allowing investigation of the laser-induced fluorescence intensities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…f and thus a are a function of environmental conditions. In particular, f decreases with increasing temperature [37,38,39]. In our experiments, we estimate this to cause a systematic error of up to 35% in magnitude, such that the measurement always tends to underestimate the real film thickness.…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…f and thus a are a function of environmental conditions. In particular, f decreases with increasing temperature [37,38,39]. In our experiments, we estimate this to cause a systematic error of up to 35% in magnitude, such that the measurement always tends to underestimate the real film thickness.…”
Section: Methodsmentioning
confidence: 81%
“…The following section gives a brief overview of the fluorescence technique employed to image liquid-film thickness. Further details on the experimental technique and some results can be found in [37,38,39].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the film temperature follows the piston temperature quite well during the cycle. Quantitative LIF fuel-film imaging on the piston window of an optical DISI engine was recently performed by Geiler et al [20]. An important outcome was that, when performing LIF fuel-film imaging, the interfering LIF signal from the gas phase is suppressed by quenching by oxygen.…”
Section: Introductionmentioning
confidence: 99%